EVALUATION OF OUTPATIENT KNOWLEDGE LEVEL ON BEYOND USE DATE IN THE USE OF THAYYIB PHARMACEUTICAL PREPARATIONS AT SUNAN KALIJAGA REGIONAL HOSPITAL DEMAK - Lestari Nurmayanti; Febrinasari, Nisa; Baiti , Mustika (SAINS INDONESIANA, 2025)
One of the key indicators for determining whether a medication is still suitable for use is the Beyond Use Date (BUD). The use of medications beyond their BUD equates to administering drugs whose stability and effectiveness are no longer guaranteed, potentially resulting in therapeutic failure and endangering patient health. In Islam, maintaining health and the environment is considered a form of spiritual responsibility,which should be implemented in everyday life. Using  edications with assured stability and effectiveness reflects an individual's accountability towards their own well-being.This study employed a descriptive observational method with a cross-sectional approach. Data were collected through a questionnaire consisting of 8 items, using purposive sampling on 99 outpatients at Sunan Kalijaga Regional General Hospital, Demak, who met the inclusion criteria. The results showed that the majority of respondents (80 individuals or 81%) had good knowledge regarding the Beyond Use Date. These findings can serve as input for the hospital, particularly pharmaceutical personnel, to maintain and improve the delivery of information and counseling about BUD to patients.